#GomorraLaSerie: Converging audience and enhanced authorship on twenty-first-century Italian screens. Issue 4 (November 2015) - Erbaggio, Pierluigi
Abstract : Based on Roberto Saviano's book Gomorra (2006), production of the TV series Gomorra – La serie (2014) was met with scepticism as many feared it would glamorise organised crime and, consequently, attract young people toward Camorra affiliation. The series' bleak portrayal of criminals and criminality was offered as a response to such concerns. Despite the preoccupations, Gomorra – La serie was hugely successful and, because of its quality, was sold to other countries. In Italy, the series' success can be measured by the popularity of its Twitter hashtag # GomorraLaSerie . Engaged with Henry Jenkins' theories of media convergence and based on a corpus of tweets bearing this official hashtag, this article proposes a quantitative analysis and advances conclusions regarding the Italian TV audience and second-screen viewing practices. Additionally, through a qualitative study of Saviano's tweets about the series, it examines the writer's use of the social media platform as a tool of narrative continuity. Finally, the article highlights a few examples of fan-generated media and concludes with remarks regarding Saviano's problematic position at the centre of a transmedia object.